2022
DOI: 10.1146/annurev-genet-071819-103933
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer Function and Evolutionary Roles of Human Accelerated Regions

Abstract: Human accelerated regions (HARs) are the fastest-evolving sequences in the human genome. When HARs were discovered in 2006, their function was mysterious due to scant annotation of the noncoding genome. Diverse technologies, from transgenic animals to machine learning, have consistently shown that HARs function as gene regulatory enhancers with significant enrichment in neurodevelopment. It is now possible to quantitatively measure the enhancer activity of thousands of HARs in parallel and model how each nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 78 publications
0
27
0
Order By: Relevance
“…In line with these data, a number of genes that are regulated by HARs with empirically confirmed or bioinformatically predicted enhancer activity, are implicated in human-specific development of certain brain areas, including the cortex (9,23,26,46,47) [also reviewed in Levchenko et al (12)]. For example, Capra et al demonstrated that 60% of HARs are enhancers and bind at least one transcription factor different between human and chimpanzee (46).…”
Section: Human Accelerated Regions and Psychosismentioning
confidence: 88%
See 2 more Smart Citations
“…In line with these data, a number of genes that are regulated by HARs with empirically confirmed or bioinformatically predicted enhancer activity, are implicated in human-specific development of certain brain areas, including the cortex (9,23,26,46,47) [also reviewed in Levchenko et al (12)]. For example, Capra et al demonstrated that 60% of HARs are enhancers and bind at least one transcription factor different between human and chimpanzee (46).…”
Section: Human Accelerated Regions and Psychosismentioning
confidence: 88%
“…There are several different types of genetic variants present in Homo sapiens, but absent in all other primate, mammalian or vertebrate species, tested so far. The rationale for studying these human-specific variants is that they could be responsible for traits specific to our species, of which the human brain is the most outstanding (9,12,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). These sequence variants include humanspecific accelerated single nucleotide substitutions in evolutionarily conserved regions called human accelerated regions (HARs) (26)(27)(28)(29)(30)(31)(32).…”
Section: Human Accelerated Regions and Psychosismentioning
confidence: 99%
See 1 more Smart Citation
“…The relatively higher cognitive play and social communication abilities revealed here should thus be stressed to help caregivers conduct language studies of MWS patients. In humans, accelerated genomic regions (ARs, the fastest-evolving sequences in the genome) are postulated as having neurological functions, potentially related to the evolution of larger brains and language ( Whalen and Pollard, 2022 ). ARs have been identified as enriched in noncoding regions near genes with known speech functions in humans and vocal learning birds, including ZEB2 , and this convergent evolution might be an indication of the particular importance of ZEB2 in vocal acquisition ( Kamm et al, 2013 ; Oksenberg et al, 2013 ; Boyd et al, 2015 ; Cahill et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Human AUTS2 display nucleotide variants that define the human-Neanderthal sweep 3 and three human accelerated regions (HARs) 4,5 .…”
Section: Introductionmentioning
confidence: 99%